Penerapan Manajemen Pendidikan dalam Mewujudkan Visi Sekolah ( MAN 1 Medan) - Wasiyem; Riska Apriani; Rina Yanti; Siti Hajar; M. Yusuf Lubis (STID Raudlatul Iman Sumenep, 2023)
School management is related to whether or not school goals are achieved in accordance with the school’s vision and mission. Therefore, to achieve this goal the principal must have good humanitarian skills. Because the position of the headmaster is a determining factor, the driver of all sources in the school, he must be able to maximize all existing components so as to improve the quality of education as a school goal. The quality of education is something that must be achieved by every educational institution as a result of the learning process for students at school. In addition, Islamic Education must also be used as a benchmark in improving the quality of education which is the responcibility of the principal in carrying out is managerial effectiveness at school. The purpose of this study is to describe how the principal managerial leadership in improving the quality of Islamic Education. This study uses a qualitative approach with the method of direct observation, in-depth interviews and documentation. The results of data analysis show that the principal’s leadership in improving the quality of Islamic Education has run quite effectively and in accordance with school policies and planning. Manajemen sekolah berkaitan dengan tercapai atau tidaknya tujuan sekolah yang sesuai dengan visi dan misi sekolah. Oleh karena itu, untuk mencapai tujuan tersebut kepala sekolah harus mempunyai kemampuan manajerial yang baik. Karena kedudukan kepala sekolah adalah sebagai faktor penentu, penggerak segala sumber yang ada di sekolah, maka ia harus mampu memaksimal segala komponen yang ada sehingga dapat meningkatkan mutu pendidikan sebagai tujuan sekolah. Mutu pendidikan menjadi hal yang harus dicapai oleh setiap lembaga pendidikan sebagai hasil dalam proses pembelajaran bagi peserta didik di sekolah. Selain itu, Pendidikan Agama Islam juga harus dijadikan tolok ukur dalam meningkatkan mutu pendidikan yang menjadi tanggung jawab kepala sekolah dalam menjalankan keefektifan manjerialnya di sekolah. Tujuan dari penelitian ini adalah untuk mendeskripsikan bagaimana kepemimpinan manajerial kepala sekolah dalam meningkatkan mutu Pendidikan Agama Islam. Penelitian ini menggunakan pendekatan kualitatif dengan metode observasi langsung, wawancara mendalam dan dokumentasi. Hasil analisis data menunjukanbahwa kepemimpinan manajerial kepala sekolah dalam meningkatkan mutu Pendidikan Agama Islam telah berjalan cukup efektif dan sesuai dengan kebijakan dan perencanaan sekolah.